Studies on the Protein Defect in Tangier Disease: ISOLATION AND CHARACTERIZATION OF AN ABNORMAL HIGH DENSITY LIPOPROTEIN - Lux, Samuel E. (1972)
High density lipoproteins (d 1.063-1.210 g/ml) were isolated from the plasma of normal individuals (HDL) and seven homozygous patients with Tangier disease (HDLt). In Tangier patients, the concentration of protein in the high density region (HDLt) was only 0.5-4.5% of normal. Immunochemical studies, including mixing experiments conducted in vivo and in vitro, indicated that HDLt was different from HDL. HDLt was the only high density lipoprotein detectable in the plasma of Tangier homozygotes. In heterozygotes both HDL and HDLt were present. HDLt was not detected in the plasma of over 300 normal persons and 10 patients with secondary high density lipoprotein deficiency and appeared to be a unique marker for Tangier disease. ApoHDL contained two major apoproteins designated apoLp-Gln-I and apoLp-Gln-II; together they comprised 85-90% of the total protein content. Both of the major HDL apoproteins were present in apoHDLt; but apoLp-Gln-I was disproportionately decreased with respect to apoLp-Gln-II, the ratio of their concentrations being 1: 12 in apoHDLt as compared with 3: 1 in apoHDL. Several minor apoprotein components which together comprise 5-15% of apoHDL were present in approximately normal proportions in apoHDLt. In the HDL of Tangier patients it was estimated that, compared with normal individuals, the concentration of apoLp-Gln-I was decreased about 600-fold and the concentration of apoLp-Gln-II about 17-fold. The decrease in these apoproteins was not due to preferential segregation with the lipoprotein fractions of d < 1.063 g/ml or with the plasma proteins of d > 1.21 g/ml. Tangier apoLp-Gln-I and apoLp-Gln-II appeared to be immunochemically identical with their normal counterparts, and no differences between the two sets of apoproteins were detected on polyacrylamide gel electrophoresis at pH 9.4 or 2.9. These results are most compatible with the hypothesis that the hereditary defect in Tangier disease is a mutation in an allele-regulating synthesis of apoLp-Gln-I.